Attenuation processes in positive social emotion upregulation: Disentangling functional role of ventrolateral prefrontal cortex - Dmitriy D. Bezmaternykh; Mikhail Ye. Melnikov; Evgeny D. Petrovskiy; Ksenia G. Mazhirina; Andrey A. Savelov; Mark B. Shtark; Patrik Vuilleumier; Yury Koush (iScience)
Summary: Positive emotions determine individual well-being and sustainable social relationships. Here, we examined the neural processes mediating upregulation of positive social emotions using functional magnetic resonance imaging in healthy female volunteers. We identified brain regions engaged in upregulation of positive social emotions and applied a parametric empirical Bayes approach to isolate modulated network connectivity patterns and assess how these effects relate to individual measures of social perception. Our findings indicate that upregulation of positive social emotions shapes the functional interplay between affective valuation and cognitive control functions. We revealed a selective increase of bilateral posterior ventrolateral prefrontal cortex (vlPFC) activity and attenuation of activity in right anterior vlPFC under control influences from more superior prefrontal regions. We also found that individual perception of sociality modulates connectivity between affective and social networks. This study expands our understanding of neural circuits required to balance positive emotions in social situations and their rehabilitative potential.